2011
DOI: 10.1007/s10681-011-0455-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping provides evidence for the role of additive and non-additive QTLs in the response of inter-specific hybrids of Eucalyptus to Puccinia psidii rust infection

Abstract: Eucalypts are susceptible to a wide range of diseases. One of the most important diseases that affect Eucalyptus plantations worldwide is caused by the rust fungus Puccinia psidii. Here, we provide evidence on the complex genetic control of rust resistance in Eucalyptus inter-specific hybrids, by analyzing a number of full-sib families that display different patterns of segregation for rust resistance. These families are totally unrelated to those previously used in other inheritance studies of rust resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Miranda et al (2013) observed strong genetic control associated with rust resistance between provenances of E. grandis. For resistance in interspecific Eucalyptus hybrids to P. psidii, Alves et al (2012) observed that quantitative additive and epistatic trait loci explain between 29.8 and 44.8% of the phenotypic variation, respectively. This is evidence of a more complex inheritance pattern of the trait.…”
Section: Resultsmentioning
confidence: 99%
“…Miranda et al (2013) observed strong genetic control associated with rust resistance between provenances of E. grandis. For resistance in interspecific Eucalyptus hybrids to P. psidii, Alves et al (2012) observed that quantitative additive and epistatic trait loci explain between 29.8 and 44.8% of the phenotypic variation, respectively. This is evidence of a more complex inheritance pattern of the trait.…”
Section: Resultsmentioning
confidence: 99%
“…Mapping studies have revealed a major contribution of both additive and non-additive (epistasis) genetic variation to disease resistance, supporting the hypothesis of complex interaction and possible successful clonal selection in which all genetic effects can be readily captured (Jorge et al 2005;Alves et al 2012). Thanks to association genetics, La Mantia et al (2013) …”
Section: Biotic Stressesmentioning
confidence: 71%
“…However, to ensure the long-term success and to simplify the selection of resistant progeny plants, the genetic control of the trait must be known for the transfer of resistance using controlled crosses. The inheritance of rust resistance in eucalypts, studied since the early 2000s (Junghans et al 2003a, Teixeira et al 2009, Rosado et al 2010, Alves et al 2011b, has shown different models to explain the segregation patterns. In the present study, we tested three models of the genetic control of resistance based on major-effect genes to explain the resistance segregation in progenies of E. pellita (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the locus Ppr1 was placed on a genetic reference map of eucalypts in linkage group 3 and was validated in two unrelated families, confirming the hypothesis that Ppr1 controls a great portion of the variation in rust resistance (Mamani et al 2010). However, further studies, particularly in interspecific hybrids progenies indicated that the genetic control of rust resistance is complex (Teixeira et al 2009, Alves et al 2011b). …”
Section: Introductionmentioning
confidence: 83%